Selective use of vandetanib in the treatment of thyroid cancer - Fallahi P; Di Bari F; Ferrari SM; Spisni R; Materazzi G; Miccoli P; Benvenga S; Antonelli A (Dove Medical Press, 2015)
Poupak Fallahi,1 Flavia Di Bari,2 Silvia Martina Ferrari,1 Roberto Spisni,3 Gabriele Materazzi,3 Paolo Miccoli,3 Salvatore Benvenga,2 Alessandro Antonelli1 1Department of Clinical and Experimental Medicine, University of Pisa, Pisa, 2Department of Clinical and Experimental Medicine, Section of Endocrinology, University of Messina, Messina, 3Department of Surgical, Medical, Molecular Pathology and Critical Area, University of Pisa, Pisa, Italy Abstract: Vandetanib is a once-daily orally available tyrosine kinase inhibitor that works by blocking RET (REarranged during Transfection), vascular endothelial growth factor receptor (VEGFR-2, VEGFR-3), and epidermal growth factor receptor and to a lesser extent VEGFR-1, which are important targets in thyroid cancer (TC). It is emerging as a potentially effective option in the treatment of advanced medullary thyroid cancer (MTC) and in dedifferentiated papillary thyroid cancer not responsive to radioiodine. The most important effect of vandetanib in aggressive MTC is a prolongation of progression-free survival and a stabilization of the disease. Significant side effects have been observed with the vandetanib therapy (as fatigue, hypertension, QTc prolongation, cutaneous rash, hand-and-foot syndrome, diarrhea, etc), and severe side effects can require the suspension of the drug. Several studies are currently under way to evaluate the long-term efficacy and tolerability of vandetanib in MTC and in dedifferentiated papillary TC. The efficacy of vandetanib in patients with MTC in long-term treatments could be overcome by the resistance to the drug. However, the effectiveness of the treatment could be ameliorated by the molecular characterization of the tumor and by the possibility to test the sensitivity of primary TC cells from each subject to different tyrosine kinase inhibitor. Association studies are evaluating the effect of the association of vandetanib with other antineoplastic agents (such as irinotecan, bortezomib, etc). Further research is needed to determine the ideal therapy to obtain the best response in terms of survival and quality of life. Keywords: vandetanib, medullary thyroid cancer, papillary thyroid cancer, tyrosine kinase inhibitors, adverse events